An assessment of training volume in professional rugby union and its impact on the incidence, severity, and nature of match and training injuries - Brooks, J. H. M.; Fuller, C. W.; Kemp, S. P. T.; Reddin, D. B. (Journal of Sports Sciences, 2008)
A prospective cohort study was used to assess the influence of training volume on injuries sustained by 502 professional rugby union players in England. Training volumes (excluding warm-ups, cool-downs, and recovery sessions), player injuries, and player match exposure times were reported weekly. Higher training volumes (9.1 hours per week) did not increase the incidence of match or training injuries. However, higher training volumes did increase the severity of match injuries, particularly during the second half, and consequently resulted in a significant increase in the number of days' absence due to match injuries. Although lower-limb injuries were the most common match and training injuries, shoulder dislocations/instabilities resulted in more days' absence during weeks of higher training volumes, but the differences were not significant. The least number of days lost due to injuries occurred during weeks of intermediate training volumes (6.2-9.1 h per week). Training volume was not correlated with final league position. Fitness testing, defence, and rucking and mauling components were identified as being very high- or high-risk training activities. Our results provide evidence of the benefits of modifying the volume and content of rugby union training to reduce the risk associated with injuries to professional players.